Effectiveness of Sandals Combined with Physical Therapy Versus Physical Therapy Alone on Pain and Function in Plantar Fasciitis: A Randomised Controlled Trial - Lunsarn, Thanwarat; Hunsawong, Torkamol; Thanasootr, Kanok-On; Chanavirut, Raoyrin; Chatchawan, Uraiwan; Boonprakop, Yodchai (Malaysian Journal of Medical Sciences, 2025)
Background: Recent evidence suggests that appropriate footwear can facilitate recovery in individuals with plantar fasciitis. This study evaluated the effectiveness of combining arch-supportive, shock-absorbing flip-flop sandals with physical therapy (PT) compared to PT alone in treating plantar fasciitis. Methods: Sixty-six participants aged 20–60 years with normal body mass index and plantar fasciitis (median symptom duration = 6 months) were randomised into either an intervention group (n = 33; PT plus sandals) or a control group (n = 33; PT alone). Both groups received eight weeks of PT and home exercises. Outcome measures were assessed at baseline, four weeks, and eight weeks and included pain-related parameters, pressure pain threshold, the Foot Function Index, and the Lower Extremity Functional Scale. The global rating of change was evaluated at weeks four and eight. Results: Both groups demonstrated significant improvements across all outcome measures (P < 0.001). A significant time × group interaction was observed for first-step post-inactivity pain (F = 3.238, P = 0.042), with the intervention group showing greater improvement (mean reduction: 3.71 points, d = 2.01) compared to controls (mean reduction: 2.82 points, d = 1.30). Improvements in all other outcome measures were comparable between the groups. Conclusion: While PT effectively improves plantar fasciitis symptoms, adding sandals provided significantly greater improvement in first-step post-inactivity pain. Further large-scale trials with extended follow-up are warranted to confirm these findings and assess long-term efficacy.